Prolonged asystole induced by trigeminocardiac reflex accompanied with abnormal heart rate variability during percutaneous balloon compression: a case report. Issue 1 (January 2023) - Zhang, Huanhuan; He, Jinhua; Du, Yanru; Liu, Meinv; Li, Jianli
Trigeminocardiac reflex (TCR) can result in bradycardia and even cardiac arrest, and is reversible with elimination of the stimulus. Here, we report the case of a 68-year-old man who experienced cardiac arrest during percutaneous balloon compression for the treatment of trigeminal neuralgia. In this patient, sinus rhythm did not recover after stimulation removal, causing us to successfully perform cardiopulmonary resuscitation (CPR). The patient regained a sinus rhythm and was pretreated with atropine 0.5 mg, allowing the operation to be started again. The operation was completed successfully and the patient experienced no complications. Subsequent heart rate variability (HRV) analysis showed that parasympathetic activity predominated before anesthesia induction and after tracheal intubation. It further elevated during foramen ovale puncture, leading to prolonged asystole. Fortunately, sympathetic activity predominated after atropine was administered, which manifested as an increase in sympathetic activity and a decrease in parasympathetic activity. This could be beneficial for patients with TCR. This case indicates that TCR-related cardiac arrest might not be reversed with stimulus cessation, and atropine played a key role in preventing TCR. Moreover, HRV analysis might be essential for preoperative screening for high-risk patients. We also reviewed the literature for cases of TCR with prolonged asystole.